Results of a new antiglaucomatous operation of non-penetrating type in patients with secondary glaucoma (clinical cases) - O.A. Rumyantseva; E.A. Korchuganova; A.Yu. Kazantzeva (РМЖ "Клиническая офтальмология")
O.A. Rumyantseva, E.A. Korchuganova, А.Yu. Kazantseva Pirogov Russian National Research Medical University, Moscow, Russian Federation Abstract Post-thrombotic glaucoma occurs as a complication in retinal hypoxic diseases, especially often — ischemic form of central retinal vein (CRV) occlusion. The glaucoma develops in about 15% of patients after 2–3 months following CRV thrombosis, complicated by an appearance of newly formed vessels and connective tissue in the corner of anterior chamber. We observed 2 patients with post-thrombotic decompensated glaucoma. The secondary glaucoma developed on average 3.5 years after the CRV thrombosis. Use of antihypertensive drops gave only a temporary effect of intraocular pressure (IOP) compensation. The patients underwent a surgical operation in volume of non-penetrating deep sclerectomy. As a result of the treatment, in all cases it was possible to compensate for the IOP, as well as to slightly increase visual acuity, to widen peripheral fields of vision and to reduce drip regime. The sclerectomy is a microinvasive non-penetrating operation, in which complications such as uveitis, postoperative hypotension, hyphema, ciliochoroidal detachment, and expulsive hemorrhage, occurring in other types of antiglaucomatous operations, are excluded. The operation is low-traumatic and conducted under local instillation anesthesia. Non-penetrating character allows, using such operations at the earliest stages of glaucoma development, preventing its further progress. Key words: post-thrombotic glaucoma, non-penetrating deep sclerectomy, sclerectomy, microinvasive surgery, uveoscleral outflow, antiglaucomatous operation, secondary glaucoma, central retinal vein thrombosis. For citation: Rumyantseva O.A., Korchuganova E.A., Kazantseva А.Yu. Results of a new antiglaucomatous operation of non-penetrating type in patients with secondary glaucoma (clinical cases). RMJ “Clinical ophthalmology”. 2018;3:150–154.